1987
DOI: 10.1680/macr.1987.39.138.42
|View full text |Cite
|
Sign up to set email alerts
|

Punching shear tests on steel-fibre-reinforced micro-concrete slabs

Abstract: Synopsis Investigations of the behaviour and strength characteristics of steel-Jihre-reinforced micro-concrete slabs subjected to punching shear are presented and discussed. A total of 12 simply-supported square slabs were tested. The parameters varied were the volume fraction of the fibres, the amount of tensile reinforcement and the concrete strength. The test results confirm that an increase infibre content improved the shear strength of the slabs; the position of the critical shear perimeter around the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 2 publications
1
53
0
Order By: Relevance
“…The experimental data is used to assess the strength predictions according to the models proposed by Narayanan and Darwish [6], Harajli et al [8] and Higashiyama et al [16], and the results obtained are shown in Fig. 11.…”
Section: Comparison To Other Prediction Modelsmentioning
confidence: 99%
See 4 more Smart Citations
“…The experimental data is used to assess the strength predictions according to the models proposed by Narayanan and Darwish [6], Harajli et al [8] and Higashiyama et al [16], and the results obtained are shown in Fig. 11.…”
Section: Comparison To Other Prediction Modelsmentioning
confidence: 99%
“…(B.1) presents the simplified expression developed by Narayanan and Darwish [6] to estimate the ultimate punching shear strength of FCR slabs. where k s is the size effect factor that depends on the slab depth h; …”
Section: B1 Model By Narayanan and Darwish [6]mentioning
confidence: 99%
See 3 more Smart Citations